SEQUENCE ANALYSIS OF TOLL-LIKE RECEPTOR9 GENE IN VECHUR CATTLE - R.Lakshmi; K.K. Jayavardhanan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Toll-like receptors (TLRs) are considered as key sensors to trigger the host innate and adaptive immune responses by recognizing various PAMPs and initiating signal transduction. TLR9 mediates the recognition of unmethylated CpG dinucleotide motifs commonly found in both bacterial and viral genomes. Vechur cattle, a rare breed of Bosindicus, are highly disease resistant compared to crossbreed animals.The study was undertaken to characterize the TLR9 gene in Vechur cattle to provide an insight into the mechanisms involved in disease resistance. Nucleotide sequence of TLR9 mRNA in Vechur revealed ORF of 3090 bp coding of 1029 aminoacids. Sequence analysis of TLR9mRNA of Vechur with Bostaurus sequence showed 99 per cent homology and exposed 5 nucleotide variations (2 non-synonymous and 3 synonymous substitutions). EighteenLRR domains were identified for TLR9 in Vechur cattle, of which LRR17 domain showed variation for one amino acid. Protein composition showed highest per cent of leucine (18.56 %) and serine (8.84%) amino acid and structure displayed contributing of alpha helix (40.72%), beta turn (19.05 %) and random coil (40.23 %). Phylogenetic tree showed all bovidae family falling under the same group, indicated conserved nature of TLR9 gene. Sequence variations observed for TLR9 gene in the Vechur cattle make this gene a likely candidate for studying variations observed in the resistance to disease at the phenotypic level.